2013
DOI: 10.1097/mao.0b013e31828399da
|View full text |Cite
|
Sign up to set email alerts
|

Revision Cochlear Implantation With Different Electrodes Can Cause Incomplete Electrode Insertion and Poor Performance

Abstract: In this study, full electrode insertion was achieved in all cases where the same type of electrode was used during initial and revision CI. In contrast, we noticed incomplete insertion in 4 of 5 patients who had revision electrodes that differed from initial electrodes. While incomplete electrode insertion does not necessitate poor speech performance, some patients with incomplete electrode insertion certainly experience it. Therefore, electrode selection requires circumspection in revision CI. Choosing a thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Each group had a mean of more than 4 years of listening experience with the initial device at the time of revision cochlear implantation. This finding is in line with previous reports 6,14,15 indicating the incidence of revision surgery to be within the first 5 years of listening experience. The familiarity of the electric signal may have allowed for the fast-rate restoration in speech perception abilities for both groups.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Each group had a mean of more than 4 years of listening experience with the initial device at the time of revision cochlear implantation. This finding is in line with previous reports 6,14,15 indicating the incidence of revision surgery to be within the first 5 years of listening experience. The familiarity of the electric signal may have allowed for the fast-rate restoration in speech perception abilities for both groups.…”
Section: Discussionsupporting
confidence: 93%
“…Other potential influences on postrevision outcomes may include differences in the intracochlear position of the revised device, upgrades in internal and external technologies, and use of new signal coding strategies. Shin et al 14 discussed the complications associated with implanting an electrode different from the initial device, including incomplete insertion depth. Four of the 5 patients who received an electrode array different from the initial device experienced incomplete electrode insertions with variable postrevision speech perception outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…8 One factor responsible for incomplete insertion was the use of a different electrode from the previous one in revision surgery. 9 Shin et al . (2013) reported that four of five patients who had to be implanted with a different electrode in revision surgery had incomplete insertion; three of these patients were implanted with a thicker electrode.…”
Section: Discussionmentioning
confidence: 99%
“…(2013) reported that four of five patients who had to be implanted with a different electrode in revision surgery had incomplete insertion; three of these patients were implanted with a thicker electrode. 9…”
Section: Discussionmentioning
confidence: 99%
“…Various surgical complications arising during cochlear reimplantation were identified as the most common reason for poor outcomes. Incomplete insertions usually occur in 7% to 18% of cases ( Côté, Ferron, Bergeron, & Bussières, 2007 ; Lassig et al., 2005 ; Shin, Park, Lee, Kim, & Choi, 2013 ) most likely due to cochlear duct obstructions as a result of fibrosis or ossification that occurs following the first implantation ( Alexiades et al., 2001 ; Côté et al., 2007 ; Miyamoto, Svirsky, Myres, Kirk, & Schulte, 1997 ). This may lead to a reduced number of channels being available for stimulation and more limited mapping options, which may affect perceptual outcomes.…”
Section: Discussionmentioning
confidence: 99%